Exploring the Role of Political Communication in Shaping Public Perceptions of Corruption - Sitti Umrah (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This research looks at how messages about politics affect how the public views misconduct. The study uses a mixed-methods strategy, gathering survey data and analyzing the content of news media coverage to draw the conclusion that the public has a negative view of corruption and that it is a serious threat to the country's economic and social progress. The study emphasizes the need for the government to successfully communicate its anti-corruption efforts to the public through the media and other channels, as well as the importance of political communication in shaping public perceptions of corruption. This research adds to the growing body of literature on corruption and political communication and has significant implications for policymakers and stakeholders..